‘Manly hearted’ Mycenaeans (?): challenging preconceptions of warrior ideology in Mycenae’s Grave Circle B - Leith, Kristin E. (Journal of Greek Archaeology, 2016)
This article investigates the distribution of weaponry in what is arguably one of the most important and distinctive archaeological sites in Greece, a funerary site that is seen as the starting point on the mainland for the expression and aggrandisement of the male Mycenaean warrior in death. The Shaft Graves are made up of two walled burial precincts, known as Grave Circle A, and Grave Circle B, the first located within and the other just outside the fortification walls of Mycenae in the region of the Argolid in the north-eastern Peloponnese on the Mainland of Greece. Most likely built by an elite kin group or groups vying to establish something akin to dynastic power, they are the richest graves documented on Mainland Greece up to that time and represent a momentous ideological shift in Mycenaean culture that took place on the mainland of Greece, c. 1700–1450 BC. Grave Circle B came into use first, and Grave Circle A shortly thereafter. Both cemeteries were active from the MHIII to LHII periods.